CCAFS Contributes to the Revision of the Climate Change Strategy and Action Plan for the Southern African Development Community - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Through its appointment to the Southern African Development Community (SADC) Secretariat’s climate change expert group, CCAFS contributed directly to the revision of the SADC Climate Change Strategy and Action Plan (2020-2030). CCAFS engaged with a range of experts to assist with thematic expertise and contributions. Through strategic content input and coordination activities, the Climate Change Strategy was updated and strengthened on aspects of climate-smart agriculture and sustainable land use, as well as on the inclusion of gender and youth considerations.